Innovative Approaches to Learning and Teaching in Ukrainian Higher Education - Nikitchenko, Liliya; Davydova, Zhanna; Krylova, Vselena; Samborska, Olena; Arkushyna, Hanna (Cadernos de Educação, Tecnologia e Sociedade, 2024)
In response to the evolving education, this research investigates innovative approaches to learning and teaching within Ukrainian higher education. The objective of this research is to compile and evaluate a range of innovative approaches utilized in higher education. This research adopts a qualitative methodology that grounded in a comprehensive analysis of extant literature. The findings of the research reveal a rich tapestry of innovative approaches within Ukrainian higher education. Synthesizing diverse insights, the study illuminates the interplay between student-centered technology integration, cross-disciplinary collaboration, and competency-based education. This research concludes by highlighting the significance of innovative approaches in education. The identified practices contribute to a more dynamic and effective learning environment, aligning educational practices with trends. The study underscores the adaptability and resilience of Ukrainian higher education institutions in embracing innovative pedagogies. Em resposta à evolução da educação, esta investigação investiga abordagens inovadoras à aprendizagem e ao ensino no ensino superior ucraniano. O objetivo desta pesquisa é sintetizar e analisar diversas abordagens inovadoras empregadas no ensino superior. Esta pesquisa adota uma metodologia qualitativa baseada em uma análise aprofundada da literatura existente. As conclusões da investigação revelam uma rica tapeçaria de abordagens inovadoras no ensino superior ucraniano. Sintetizando diversos insights, o estudo ilumina a interação entre a integração tecnológica centrada no aluno, a colaboração interdisciplinar e a educação baseada em competências. As práticas identificadas contribuem para um ambiente de aprendizagem mais dinâmico e eficaz, alinhando as práticas educativas às tendências. O estudo sublinha a adaptabilidade e resiliência das instituições de ucranianas na adoção de pedagogias inovadoras.